Financial Integration, Financial Development, and Global Imbalances - Mendoza, Enrique G.; Quadrini, Vincenzo; Ríos‐Rull, José‐Víctor (Journal of Political Economy, 2009)
Global financial imbalances can result from financial integration when countries differ in financial markets development. Countries with more advanced financial markets accumulate foreign liabilities in a gradual, long-lasting process. Differences in financial development also affect the composition of foreign portfolios: countries with negative net foreign asset positions maintain positive net holdings of nondiversifiable equity and foreign direct investment. Three observations motivate our analysis: (1) financial development varies widely even among industrial countries, with the United States on top; (2) the secular decline in the U.S. net foreign asset position started in the early 1980s, together with a gradual process of international financial integration; (3) the portfolio composition of U.S. net foreign assets features increased holdings of risky assets and a large increase in debt. (c) 2009 by The University of Chicago. All rights reserved.